(untitled) (Acta Entomologica Serbica, 2017)
In studying the fauna of cynipid gall wasps of Belgrade and its environs during the period from 1997 to 2016, we recorded a total of 46 species from four tribes (Aylacini, Cynipini, Diastrophini and Diplolepidini) and 12 genera (Andricus, 27 species; Diplolepis, 5 species; Cynips, 3 species; Neuroterus, 3 species; Diastrophus, 2 species; Aphelonyx, 1 species; Barbotinia, 1 species; Biorhiza, 1 species; Callirhytis, 1 species; Chilaspis, 1 species; Dryocosmus, 1 species; and Pseudoneuroterus, 1 species). The following species are here recorded as new for the Serbian fauna of cynipid gall wasps: Diastrophus mayri Reinhard,1876; D. rubi (Bouche, 1834); Andricus aries (Giraud, 1859); A. conificus (Hartig, 1834); A. gallaeurnaeformis (Boyer de Fonscolombe, 1832); A. grossulariae Giraud, 1859; A. inflator Hartig, 1840; A. superfetationis (Giraud, 1859); Callirhytis glandium (Giraud, 1859); and Chilaspis nitida (Giraud, 1859). For all the recorded species, we give the localities, dates and hosts on which they were found in Belgrade and its environs.